ANALISIS PEMANFAATAN e-PUSKESMAS DENGAN METODE PERFOMANCE, INFORMATION, EKONOMI, CONTROL, DAN EFISIENSI, SERVICE (PIECES) DI PUSKESMAS KOTA PADANG - Devid Leonard; Dewi Mardiawati; Dian Sari (Ensiklopedia of Journal, 2018)
Implementation of e-puskesmas in Padang City health centers is expected to contribute to health centers in improving the effectiveness and efficiency of health services. The results of observations of e-puskesmas applications are not in accordance with the needs of health center staff (from registration to reporting). To assess the benefits of implementing an e-puskesmas one of the evaluation methods that can be used is an evaluation based on the user's perception using the PIECES method. This research is a qualitative case study approach. This research was conducted at the Padang City health center from February to May 2018. The informants in this study amounted to 10 people taken by purposive sampling technique, data analysis results of Focus Group Discastion (FGD) will be carried outprocess transcription, data reduction, coding, categories, presentation data and data interpretation. Aspects of Performance input of patient data and response time is faster, in the aspect of information there are still obstacles, namely the resulting report is still limited to LB1 reports, still constrained for data briging with P-care BPJS, on theaspect the economic use of e-puskesmas still does not provide benefits which is large in terms of reporting because there are still data input activities and reporting that must be done manually. In terms ofaspects control, the implementation of e-puskesmas still faces constraints in terms of data security because all officers can access the e-puskesmas with the same user and password. For theaspects of efficiency the e-puskesmas users are still constrained by the workload of recording and reporting that is still done manually to the City Health Office, theaspect service needs to be the development of the modules in the e-puskesmas such as the LB2 to LB 4 reporting menu module. It is necessary to develop a menu / module on the e-Puskesmas system, the need for a data security system by providing login access according to the user level and the need for communication with BPJS related to briging data.